KETIKA PEREMPUAN LUPA (Etnografi Perempuan TQN, PP Suryalaya, Tasikmalaya-Jawa Barat) - Ade Yamin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This ethnographic study shows that, the conception of gender equality is interpreted by Suryalaya TQN community is a result of discrimination on gender in the form of male domination of women. This happens because, for dogmatic reasons and traditions, or precisely because women have been shown to surrender to what happened so long in the community. Therefore, efforts need to begin to affect the habits that put the subordination of women as men, through lectures, explanations to the provision of community models TQN Suryalaya in looking at the presence of women.